Muslim laws (New Delhi, 2012)
This publication is being sold on the condition and understanding that the information, comments, and views it contains are merely for guidance and reference and must not be taken as having the authority of, or being binding in any way on, the author, editors, publishers, and sellers, who do not owe any responsibility whatsoever for any loss, damage, or distress to any person, whether or not a purchaser of this publication, on account of any action taken or not taken on the basis of this publication. Despite all the care taken, errors or omissions may have crept inadvertently into this publication. For authoritative text information, please contact the department concerned or refer to the Government publication or the Gazette notification. The publishers shall be obliged if any such error or omission is brought to their notice for possible correction in a future edition. In the case of binding defect, misprint, missing pages, etc., the publishers' liability is limited to replacement of the defective copy within one month of its purchase by a copy of the same edition or reprint. All disputes are subject to the jurisdiction of competent courts in Delhi.
Keywords: "Muslim women (protection of rights on divorce) act,1986"